Treating without diagnosis: Psychoanalysis in medical settings in Argentina - Bonnin, Juan Eduardo (2015)
This article is part of a larger research project, the aim of which is to understand the discursive conditions of access and adherence to an outpatient mental health service at a public hospital in Buenos Aires, Argentina. The focus is on the historical conflict between medical discourse and psychoanalytical discourse as it emerges in the negotiation of treatment and diagnostic sequences at first consultations. It can be seen that patients who are socialized in medical discourse - and even in psychiatric discourse - expect the usual procedure in which a diagnosis, however transitory, is offered first and then followed by a treatment recommendation. However, psychoanalysts, in contrast, tend to reject diagnostic labels and offer treatment without further justification. This has an impact on the adherence of patients, and we can argue for the need to negotiate with medical discourse in order to guarantee engagement and continuity in treatment.